Strategi Guru BK Menangani Perundungan dengan Layanan Konseling Individu di UPT SMP Negeri 29 Medan - Simanjuntak, Desy Vesya; Arta Sriyuni Bakara; Ester Juliana Amorito Samosir; Tria Febicha Oktavia Bangun; Neva Roulita Hutahaean (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Bullying is a complex phenomenon in the school environment that affects students’ psychological and academic conditions. This study aims to examine the strategies of Guidance and Counseling (BK) teachers in addressing bullying through individual counseling services at UPT SMP Negeri 29 Medan. This research employs a descriptive qualitative approach, with data collected through semi-structured interviews with two BK teachers and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results indicate that bullying occurs in both physical and verbal forms, triggered by emotional conflicts and family-related factors. The intervention is carried out through systematic individual counseling consisting of three stages: the initial stage involving service planning (RPL) and relationship building with an emphasis on confidentiality; the working stage involving problem exploration through dialogue and mediation; and the final stage involving reinforcement through written agreements as follow-up actions. Counseling services are also implemented adaptively through a “simple counseling” approach to address time limitations. The main challenges include limited time and students’ lack of honesty, which are addressed through strategy adjustments and collaboration with school personnel and parents. This study concludes that well-planned, systematic, and adaptive individual counseling is effective in addressing and preventing bullying in schools.